An uncharacterized gene Lb1G04794 from Limonium bicolor promotes salt tolerance and trichome development in Arabidopsis - Jiao, Xiangmei; Zhao, Boqing; Wang, Baoshan; Yuan, Fang (Frontiers in Plant Science, 2022)
Halophytes can grow and reproduce in high-salinity environments, making them an important reservoir of genes conferring salt tolerance. With the expansion of saline soils worldwide, exploring the mechanisms of salt tolerance in halophytes and improving the salt tolerance of crops have become increasingly urgent. Limonium bicolor is a halophyte with salt glands that secrete excess Na+ through leaves. Here, we identified an uncharacterized gene Lb1G04794, which showed increased expression after NaCl treatment and was high during salt gland development in L. bicolor. Overexpression of Lb1G04794 in L. bicolor showed promoted salt gland development, indicating that this gene may promote salt gland differentiation. Transgenic Arabidopsis strains overexpressing Lb1G04794 showed increased trichomes and decreased root hairs under normal conditions. Compared with wild type (WT), root growth in the transgenic lines was less inhibited by NaCl treatment. Transgenic seedlings accumulated less fresh/dry weight reductions under long-term salt treatment, accompanied by lower Na+ and malondialdehyde accumulation than WT, indicating that these transgenic lines behave better growth and undergo less cellular damage under NaCl stress. These results were consistent with the low expression levels of salt-tolerance marker genes in the transgenic lines upon salt stress. We conclude that the unknown gene Lb1G04794 positively regulated salt gland development, and promoted salt tolerance of Arabidopsis, offering a new direction for improving salt tolerance of non-halophytes and crops.